Undocumented Again? DACA Rescission, Emotions, and Incorporation Outcomes among Young Adults. (23rd June 2022) - Aranda, Elizabeth; Vaquera, Elizabeth; Castañeda, Heide; Martinez Rosas, Girsea
Abstract: Former President Trump's election and subsequent anti-immigrant policy initiatives brought an unprecedented sense of uncertainty for undocumented immigrants. This is particularly true for those who had experienced expanding opportunities through the Deferred Action for Childhood Arrivals (DACA) executive action signed by former President Obama in 2012. We use in-depth interviews with undocumented young adults to explore how the 2016 presidential election and 2017 executive action that rescinded DACA evoked emotions of anticipatory loss—including sadness and grief—and ontological insecurity—including anxiety and uncertainty. We adopt an interpretive and social constructionist approach to explore these emotions and their implications, demonstrating how even the threat of policy change impacts immigrant young adults' societal incorporation. We illustrate how DACA recipients conceptualized loss and how these experiences manifested in educational attainment, labor market incorporation, feelings of belonging, and civic participation. Our study provides an innovative contribution to interpret in real-time the incorporation trajectories through the emotions of living with precarious legal status.